METHODOLOGY OF THE EFFICIENCY ASSESSMENT OF THE AIR-TRANSPORT NETWORK - Марінцева, К. (Science-based technologies, 2012)
The efficiency evaluation of the country air-transport network functioning and development basic principles and methodology is described with taking into account modern tendencies of the aviation industry development.